Implementation of Shared and Webbed Learning Model in Elementary Schools: A Qualitative Study Through Interviews with Teachers - Rita, Novia; Fitria, Yanti; Erita, Yeni (International Journal of Educational Dynamics, 2023)
The development of integrated thematic learning in elementary schools is an increasingly popular approach to building foundational knowledge, skills, and positive attitudes in children. This article aims to explain the implementation of the shared and webbed learning models in elementary schools through qualitative research using teacher interviews. The research sample consisted of elementary school teachers who have implemented the shared and webbed learning models in integrated thematic learning. Data obtained from the teacher interviews were analyzed using a descriptive analysis approach to identify emerging themes and patterns. The results of the study indicate that the shared and webbed learning models have been implemented in various ways in elementary schools but also face challenges in terms of time, teacher understanding, and comprehensive assessment. The benefits obtained include improved student understanding, the development of collaborative skills, and student motivation in learning. In further development, adequate support is needed in terms of time and resources, teacher training, and the development of relevant assessment instruments to enhance the implementation of shared and webbed learning models in elementary schools.